Bioorthogonal chemistry in bioluminescence imaging - Godinat, Aurélien; Bazhin, Arkadiy A.; Goun, Elena A. (Drug discovery today, 2018)
•Bioorthogonal chemistry has broaden the scope of bioluminescence imaging.•Split luciferin based assays allow investigation of aminopeptidase activities.•Azido-modified biomolecules can be imaged using the Staudinger ligation. Bioorthogonal chemistry has developed significant over the past few decades, to the particular benefit of molecular imaging. Bioluminescence imaging (BLI) along with other imaging modalities have significantly benefitted from this chemistry. Here, we review bioorthogonal reactions that have been used to signific antly broaden the application range of BLI.